The Diversification of Rural Livelihoods After the Year 2000 in Zimbabwe - Chiba, Moffat (Advances in Social Sciences Research Journal, 2023)
The article explores rural livelihood diversification patterns after the year 2000 using the Zimbabwean case. It relied on 30 households’ life history accounts alongside document analysis by examining the processes, determinants, and outcomes of these livelihood configurations. While rural households’ livelihoods had come to entirely rely on either agriculture or wage employment or both before the 2000s, evidence has demonstrated that after the year 2000, the means of survival have been diversified into a number of a complicated archaeology of occupational testing through the streamlining of land and labour away from agriculture, and the consequent following of such occupations like hair-cutting, vending, migration among others. These livelihood patterns have been due to a complicated archaeology of events ranging from rural households’ socio-economic changes, the Fast Track Land Reform Programme, the unemployment effects of the fourth Industrial revolution and ecological destabilisation. Policy interventions, thus, need to acknowledge rural livelihoods diversification and help citizens by incorporating and helping these rural households into rural development projects and programmes to better their livelihoods.